A long-life high pressure aluminum electrolysis electrolyte composition and a method of making the same
Patent Information
- Application Number
- CN202611457324.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]针对上述问题,本申请通过构建儿茶酚-硼酸酯杂化低支化聚酯与铝-磷酸酯配位型复合溶剂协同的溶质体系,并引入消氢防水合双效剂,从分子层面将硼、磷功能性元素化学键合锚定于聚合物骨架中,同时利用蒽醌-聚乙二醇酯化物主动捕获并消耗体系中游离水分子与氢气,有效解决了传统电解液在高温下热稳定性差、水合与析氢相互耦合加速失效以及铝箔腐蚀的难题,实现了高压铝电解电容器在高温工况下的超长寿命可靠服役
[0031]本申请提供一种长寿命高压铝电解电解液组合物。本申请首先以己二酸、1,3-丙二醇及三羟甲基丙烷经熔融缩聚构建含末端活性羟基的低支化聚酯骨架,该骨架兼具适度自由体积与多位点接枝活性,为后续功能化修饰奠定结构基础;继而通过3,4-二羟基苯甲酸酯化接枝引入邻苯二酚(儿茶酚)基团,并进一步和硼酸反应形成具有缺电子B-O-C键的硼酸酯交联位点,制得儿茶酚-硼酸酯杂化低支化聚酯。其中,邻苯二酚基团通过邻位双羟基的强螯合配位能力,锚定于阳极氧化膜表面铝原子,形成稳定的五元环螯合物,有效钝化界面活性位点;硼酸酯基团则利用硼原子的Lewis酸性中心有助于降低体系游离水活度,同时其较大的空间位阻对邻近酯键产生屏蔽效应,协同提升聚酯骨架的抗热裂解与抗水解能力。
Smart Images

Figure CN122991868A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of aluminum electrolytic capacitor technology, specifically to a long-life high-voltage aluminum electrolytic electrolyte composition and its preparation method. Background Technology
[0002] Aluminum electrolytic capacitors, as indispensable basic components in electronic circuits, are widely used in frequency converters, industrial power supplies, LED lighting, and automotive electronics. With the continuous increase in reliability requirements for these applications, the market is placing increasingly stringent demands on the high-temperature resistance and long lifespan of aluminum electrolytic capacitors. The working electrolyte, as the core material of the capacitor, not only determines the leakage current, loss tangent, and operating temperature range, but also directly determines the capacitor's lifespan. In the field of high-voltage aluminum electrolytic capacitors, the working electrolyte is typically composed of solvents, solutes, and various additives, among which the molecular structure and thermal stability of the solute play a decisive role in the high-temperature performance of the electrolyte.
[0003] However, existing electrolytes for high-voltage aluminum electrolytic capacitors face severe technical bottlenecks during long-term high-temperature operation. On one hand, traditional working electrolytes often use small-molecule ammonium carboxylate salts as the main solute, which are prone to irreversible chemical reactions such as thermal decomposition, amidation, and esterification at high temperatures. This leads to a continuous decrease in electrolyte conductivity and a continuous increase in equivalent series resistance (ESR), ultimately causing capacitor capacity decay and an increase in the loss tangent. On the other hand, trace amounts of moisture inevitably exist in the electrolyte at high temperatures. This moisture reacts with the aluminum anolyte film to form hydrated alumina, damaging the insulation properties of the dielectric layer and causing a surge in leakage current. Furthermore, water molecules electrolyze under an electric field to produce hydrogen gas, causing a continuous increase in internal pressure within the capacitor, which can lead to bulging, leakage, and even the opening of the explosion-proof valve. Meanwhile, the small-molecule acidic substances released by the thermal decomposition of the solute, in synergy with high-temperature moisture, significantly enhance the corrosive activity of the electrolyte, accelerating localized chemical corrosion deep within the aluminum foil substrate and its etched holes. Furthermore, the small molecules produced by decomposition more easily penetrate into the holes, further exacerbating the damage to the electrode structure and the capacity decay process. Even more serious is the vicious cycle of these two failure mechanisms—thermal decomposition and hydration / hydrogen evolution—coupled under high-temperature conditions: the moisture produced by the thermal decomposition of the solute further intensifies the hydration and hydrogen evolution reactions, while the damage to the oxide film caused by the hydration reaction accelerates the side reactions between the electrolyte and the aluminum foil.
[0004] To address the aforementioned technical problems, existing technologies attempt to repair performance by adding various functional additives such as hydrogen scavengers and flash voltage enhancers. However, these solutions lack synergistic design at the molecular level among their components, making it difficult to fundamentally resolve the two core contradictions simultaneously: insufficient high-temperature thermal stability and hydration / hydrogen evolution corrosion. In recent years, polyester polymers have been introduced as electrolyte additives into the field of aluminum electrolytic capacitors, and studies have shown that they can improve flash voltage and thermal stability to some extent. However, existing polyester additives are mostly linear structures, lacking effective anchoring ability on the oxide film surface and lacking functional groups that actively regulate the behavior of interfacial water molecules, resulting in limited performance improvements.
[0005] In summary, there is an urgent need to develop a novel high-voltage aluminum electrolytic electrolyte composition. Through innovation in the molecular structure of solute molecules and synergy of functional components, this composition can effectively inhibit hydration, hydrogen evolution reactions, and chemical corrosion of the aluminum matrix while improving the high-temperature thermal stability of the electrolyte. This will enable high-voltage aluminum electrolytic capacitors to achieve long-life and reliable operation under high-temperature conditions. Summary of the Invention
[0006] To address the aforementioned issues, this application constructs a solute system synergistically combining a catechol-boron ester hybrid low-branched polyester with an aluminum-phosphate ester coordination-type composite solvent. It also introduces a hydrogen-removing and water-retaining dual-effect agent to chemically anchor boron and phosphorus functional elements to the polymer backbone at the molecular level. Simultaneously, anthraquinone-polyethylene glycol esters actively capture and consume free water molecules and hydrogen in the system. This effectively solves the problems of poor thermal stability of traditional electrolytes at high temperatures, accelerated failure due to the coupling of hydration and hydrogen evolution, and aluminum foil corrosion. This results in ultra-long-life and reliable operation of high-voltage aluminum electrolytic capacitors under high-temperature conditions.
[0007] To achieve the above objectives, one technical solution adopted in this application is:
[0008] In a first aspect, this application provides a long-life high-voltage aluminum electrolysis electrolyte composition, comprising a catechol-boron ester hybrid low-branched polyester, an aluminum-phosphate ester coordination type composite solvent, and an additive;
[0009] The catechol-boronic acid ester hybrid low-branched polyester is prepared by first grafting a low-branched polyester intermediate with 3,4-dihydroxybenzoic acid esterification, and then reacting it with boric acid. The low-branched polyester intermediate is prepared by esterification polycondensation reaction of adipic acid, 1,3-propanediol and trimethylolpropane.
[0010] The aluminum-phosphate coordination type composite solvent is prepared by a coordination reaction of aluminum alkoxide and alkyl phosphate in a polyol;
[0011] The additives include a hydrogen-removing and waterproofing dual-effect agent, a flash voltage booster, and a high-voltage film-forming additive.
[0012] The hydrogen-removing and waterproofing dual-effect agent is prepared by esterification grafting reaction of 1,4-dihydroxyanthraquinone-2-carboxylic acid and bi-hydroxyl-terminated polyethylene glycol.
[0013] Preferably, the aluminum alkoxide is aluminum isopropoxide or aluminum sec-butoxide; the alkyl phosphate includes at least one of monobutyl phosphate, dibutyl phosphate, monoisooctyl phosphate, and diisooctyl phosphate; the polyol includes at least one of ethylene glycol, diethylene glycol, and 1,3-propanediol; the hydroxyl-terminated polyethylene glycol is PEG400; the flashover voltage booster is mannitol or sorbitol; the high-voltage film-forming additive includes any one of phosphotungstic acid, phosphomolybdic acid, and hypophosphite; and the 1,4-dihydroxyanthraquinone-2-carboxylic acid is obtained by oxidizing 1,4-dihydroxyanthraquinone with sodium chlorite after Reimer-Tiemann formylation.
[0014] Secondly, this application provides a method for preparing a long-life, high-voltage aluminum electrolysis electrolyte composition, comprising the following steps:
[0015] S1. Adipic acid, 1,3-propanediol and trimethylolpropane are mixed to obtain a mixture. p-Toluenesulfonic acid is added, and an esterification polycondensation reaction is carried out under nitrogen protection to obtain a low-branched polyester intermediate. 3,4-Dihydroxybenzoic acid and p-toluenesulfonic acid are added, and a grafting reaction is carried out under nitrogen protection. Boron esterification reaction is added. Low-boiling substances are removed under reduced pressure to obtain a catechol-boron ester hybrid low-branched polyester.
[0016] S2. Mix and dissolve the polyol and aluminum alkoxide, add alkyl phosphate dropwise, and react under nitrogen protection; remove alcohol under reduced pressure, filter, and obtain aluminum-phosphate coordination complex solvent;
[0017] S3. 1,4-Dihydroxyanthraquinone was dispersed in an aqueous sodium hydroxide solution; anhydrous ethanol and a phase transfer catalyst were added, and chloroform was added dropwise. The two-phase reaction was carried out under reflux and condensation conditions. After the reaction was completed, the mixture was cooled, the pH was adjusted, the solid precipitated, and the solid was separated, washed, and purified to obtain 1,4-dihydroxyanthraquinone-2-carboxaldehyde. The 1,4-dihydroxyanthraquinone-2-carboxaldehyde was dispersed in a mixed medium of acetic acid and water. The pH was adjusted using glacial acetic acid, and 2-methyl-2-butene and an aqueous sodium chlorite solution were added and stirred for oxidation. After the reaction was completed, the mixture was cooled, the solid precipitated, filtered, washed with water, and dried to obtain 1,4-dihydroxyanthraquinone-2-carboxylic acid. Under nitrogen protection, 1,4-dihydroxyanthraquinone-2-carboxylic acid, PEG-400, and p-toluenesulfonic acid were mixed and grafted to obtain a hydrogen-removing and water-repellent dual-effect agent.
[0018] S4. The catechin-boron ester hybrid low-branched polyester, aluminum-phosphate ester coordination type composite solvent and hydrogen-removing and waterproofing dual-effect agent are added to the compounding kettle and mixed; flash voltage booster and high voltage film-forming additive are added and stirred and mixed, cooled to room temperature and filtered to obtain a long-life high voltage aluminum electrolytic electrolyte composition.
[0019] In the S1 process described in this application, adipic acid, 1,3-propanediol, and trimethylolpropane are stirred and mixed under a high-purity nitrogen atmosphere. The nitrogen atmosphere effectively eliminates dissolved oxygen and water vapor in the system, suppressing the oxidation and discoloration of the polyol and the etherification side reaction at high temperatures. During the esterification process, after protonation of the carboxylic acid, it undergoes a nucleophilic addition-elimination reaction with the hydroxyl group to generate ester bonds and condensation water. The continuous decrease in the acid value of the system indicates the progress of esterification. The introduction of trimethylolpropane provides a trifunctional branching node, which gradually constructs a branched polyester intermediate with ester bonds as the main chain and abundant active hydroxyl groups at the ends. These active hydroxyl groups provide a multi-site platform for subsequent functional grafting. Upon addition of 3,4-dihydroxybenzoic acid, its carboxyl group undergoes dehydration esterification with the terminal hydroxyl groups of the polyester under catalysis, covalently grafting the catechol (catechol) structure to the end of the branch chain. Subsequently, boric acid is added, and the ortho- and posterior dihydroxyl groups of the catechol undergo coordination esterification with boric acid to form a stable five-membered ring borate ester structure, constructing a catechol-boron ester hybrid low-branched network. p-Toluenesulfonic acid functions as both a polycondensation catalyst and an esterification catalyst throughout the process. At the end of the reaction, reduced pressure removes low-boiling substances, unreacted monomers, and byproduct condensation water, driving the reaction equilibrium to the right and ensuring the grafting rate and degree of borate esterification.
[0020] In step S2, a polyol and an aluminum alkoxide are heated and dissolved under nitrogen protection. The aluminum atoms in the aluminum alkoxide are in an electron-deficient state and undergo Lewis acid-base coordination with the oxygen atoms of the polyol, forming an aluminum-alcohol complex intermediate. This process effectively reduces the self-aggregation tendency of the aluminum alkoxide and improves its dispersion stability in the system. Subsequently, an alkyl phosphate is slowly added dropwise. The electronegative oxygen atoms in the phosphate groups (P=O and P—OH) compete for coordination with the coordinated aluminum atoms, gradually replacing the hydroxyl coordination sites and forming an aluminum-phosphate coordination structure with Al-OP coordination bonds. This process is exothermic, and controlling the dropping rate can effectively suppress precipitation or cross-linking side reactions caused by local overheating. After the reaction is complete, the alcohol is removed under reduced pressure to remove byproduct low-carbon alcohols and low-boiling substances. Trace amounts of insoluble matter are removed by hot filtration, yielding a clear and transparent aluminum-phosphate coordination composite solvent. The Al-OP coordination structure in this solvent has the ability to migrate directionally to defect sites in the anodic oxide film under an electric field.
[0021] In step S3, 1,4-dihydroxyanthraquinone is dispersed in an aqueous sodium hydroxide solution. Under alkaline conditions, the anthraquinone phenolic hydroxyl groups are deprotonated to form sodium phenolate, enhancing the electron cloud density of the benzene ring and activating the electrophilic substitution activity of the aromatic hydrogens on the anthraquinone ring. Anhydrous ethanol and a phase transfer catalyst are added. The phase transfer catalyst extracts and transfers the anthraquinone sodium phenolate from the aqueous phase to the organic phase via ion-pair extraction, significantly improving the oil-water two-phase mass transfer efficiency. After heating, chloroform is added dropwise. Under alkaline conditions, chloroform generates a dichlorocarbene active intermediate in situ. This intermediate undergoes electrophilic aromatic substitution of the activated anthraquinone ring, introducing a formyl precursor at the ortho position of the hydroxyl group. After substitution, the dichlorocarbene is hydrolyzed to generate an aldehyde group, yielding 1,4-dihydroxyanthraquinone-2-carboxaldehyde. After this step, the reaction is acidified to pH 2-4, causing the phenolic hydroxyl groups to reprotonate and precipitate. After washing and purification, a pure product is obtained. The obtained aldehyde compound was dispersed in an acetic acid-water mixture, and the pH was adjusted to 3.0-5.5 with glacial acetic acid to maintain a weakly acidic environment. 2-Methyl-2-butene was added as a chlorine scavenger to suppress side reactions. Sodium chlorite aqueous solution was added dropwise, and under weakly acidic conditions, sodium chlorite selectively oxidized the aromatic aldehyde group to a carboxylic acid. The aldehyde group was then converted to a carboxyl group via a nucleophilic addition-elimination process to obtain 1,4-dihydroxyanthraquinone-2-carboxylic acid. Subsequently, 1,4-dihydroxyanthraquinone-2-carboxylic acid was mixed with PEG-400 under nitrogen protection, and p-toluenesulfonic acid was added as a catalyst. The carboxylic acid and the terminal hydroxyl group of PEG underwent a dehydration esterification grafting reaction, linking the anthraquinone carboxylic acid group to the PEG chain end via an aromatic ester bond, thus preparing an anthraquinone-PEG amphiphilic covalent coupler. The flexible long chain of PEG endows the hydrogen-scavenging active center with persistent dispersion stability and interfacial migration ability in the electrolyte.
[0022] In step S4, the catechol-boron ester hybrid low-branched polyester, the aluminum-phosphate ester coordination type composite solvent, and the hydrogen-removing and water-repellent dual-effect agent are sequentially added to the compounding vessel and stirred. Within this temperature range, all components are in a low-viscosity liquid state. The polar ester groups in the polyester skeleton undergo ion-dipole and hydrogen bonding synergistic interactions with the BO and Al-OP coordination structures, forming a homogeneous and transparent precursor mixed network. In the anthraquinone-PEG coupler, the PEG segments establish hydrogen bond bridges between the polyester skeleton and solvent molecules through ether oxygen atoms, ensuring that the anthraquinone active centers are uniformly dispersed at the molecular level in the system. Subsequently, a flashover voltage enhancer and a high-voltage film-forming additive are added. The polyhydroxy structure is anchored to the polar microregions through hydrogen bonding and coordination, while phosphotungstic acid / phosphomolybdic acid undergoes secondary coordination assembly with Al-OP in the system and is effectively complexed and confined. From a thermodynamic perspective, the catechol structure and boric acid in the catechol-boron ester hybrid polyester form a stable five-membered ring chelate borate ester, with boron atoms in sp... 3The hybridized state coordinates and locks the ortho- and tho-hydroxyl groups, shifting the oxidation potential in the positive direction; simultaneously, the rigid five-membered ring structure provides a spatial shield, blocking the intramolecular electron transfer pathway required for the oxidation reaction. Therefore, the catechol-boron ester hybrid network is not easily oxidized to ortho-benzoquinone, and the anthraquinone-hydroquinone reversible pair in the hydrogen-removing and water-retaining dual-effect agent is not damaged by the oxidation of heteropolyacids. Both exhibit good redox compatibility in the system. After stirring, the mixture is cooled to room temperature, and trace mechanical impurities are removed by filtration, yielding a homogeneous, stable, long-life, high-voltage aluminum electrolytic electrolyte composition.
[0023] Preferably, in S1, the mass ratio of adipic acid, 1,3-propanediol, and trimethylolpropane is 100:(55-65):(3-8); during the esterification polycondensation reaction, the amount of p-toluenesulfonic acid added is 0.1%-0.5% of the mass of the mixture; the temperature of the esterification polycondensation reaction is 160-190°C, and the time of the esterification polycondensation reaction is 4-8 hours.
[0024] Preferably, in S1, the amount of 3,4-dihydroxybenzoic acid added is 8% to 18% of the mass of the low-branched polyester intermediate; during the grafting reaction, the amount of p-toluenesulfonic acid added is 0.5% to 1% of the mass of the 3,4-dihydroxybenzoic acid; the process parameters of the grafting reaction are: -0.06 to -0.095 MPa vacuum dehydration, temperature 120 to 140°C, and time 3 to 5 h; the amount of boric acid added is 4% to 10% of the mass of the low-branched polyester intermediate; the temperature of the esterification reaction is 80 to 95°C, and the time of the esterification reaction is 2 to 4 h; the vacuum degree for removing low-boiling substances is -0.08 to -0.095 MPa, the temperature for removing low-boiling substances is 120 to 150°C, and the time for removing low-boiling substances is 0.5 to 1 h.
[0025] Preferably, in S2, the dropping rate of the alkyl phosphate is 1-2 mL / min; the mixing and dissolving temperature is 50-80°C and the mixing and dissolving time is 0.5-1.5 h; the reaction temperature is 50-80°C and the reaction time is 4-7 h; the vacuum dehydration temperature is 80-100°C and the vacuum dehydration time is 0.5-1 h; the mass ratio of the aluminum alkoxide, alkyl phosphate, and polyol is 1:(1.1-1.8):(1.8-3).
[0026] Preferably, in step S3, the sodium hydroxide has a mass fraction of 10-30 wt%, the mass ratio of 1,4-dihydroxyanthraquinone to sodium hydroxide is 1:(0.8-1.4), and the amount of anhydrous ethanol added is 1-3 times the mass of the 1,4-dihydroxyanthraquinone; the phase transfer catalyst is TEBA (benzyltriethylammonium chloride) or TBAB (tetrabutylammonium bromide), and the amount of the phase transfer catalyst added is 0.5% of the mass of the 1,4-dihydroxyanthraquinone. ~2%, the chloroform is added dropwise at 45~65℃ and stirred at 300~500r / min, the mass ratio of chloroform to 1,4-dihydroxyanthraquinone is 1:(1~1.8); the temperature of the two-phase reaction is 60~70℃ and the reaction time is 4~7h, the pH value is 2~4; the volume ratio of acetic acid to water is 1:(1~4), and the mass ratio of 1,4-dihydroxyanthraquinone-2-formaldehyde to the mixed medium is 1:(15~40).
[0027] Preferably, in step S3, the pH value adjusted by glacial acetic acid is 3.0–5.5; the amount of 2-methyl-2-butene added is 25%–60% of the mass of 1,4-dihydroxyanthraquinone; the concentration of the sodium chlorite aqueous solution is 10–20 wt%; the amount of sodium chlorite added to the sodium chlorite aqueous solution is 45%–85% of the mass of 1,4-dihydroxyanthraquinone-2-formaldehyde; and the stirring oxidation temperature is 10–30°C, and the stirring oxidation time is 3–6 h.
[0028] Preferably, in S3, the mass ratio of 1,4-dihydroxyanthraquinone-2-carboxylic acid to PEG-400 is 1:(2-4), and the amount of p-toluenesulfonic acid added is 0.5% to 3% of the mass of 1,4-dihydroxyanthraquinone-2-carboxylic acid; the esterification grafting reaction is carried out under reduced pressure dehydration conditions of -0.06 to -0.095 MPa, the temperature of the esterification grafting reaction is 130 to 150°C, and the time is 3 to 6 hours.
[0029] Preferably, in S4, the mass ratio of the catechol-boron ester hybrid low-branched polyester, the aluminum-phosphate ester coordination composite solvent, the hydrogen-removing and waterproofing dual-effect agent, the flashover voltage booster and the high-voltage film-forming additive is (30-50):(40-60):(5-15):(1-5):(0.5-3); the stirring and mixing temperature is 70-90℃ and the time is 2-4h.
[0030] Compared with the prior art, the beneficial effects of this application are as follows:
[0031] This application provides a long-life, high-voltage aluminum electrolytic electrolyte composition. First, a low-branched polyester backbone containing terminal active hydroxyl groups is constructed by melt polycondensation of adipic acid, 1,3-propanediol, and trimethylolpropane. This backbone possesses both moderate free volume and multi-site grafting activity, laying the structural foundation for subsequent functionalization modifications. Then, catechol groups are introduced through 3,4-dihydroxybenzoic acid esterification grafting, and further reacted with boric acid to form borate ester crosslinking sites with electron-deficient BOC bonds, yielding a catechol-boron ester hybrid low-branched polyester. The catechol groups, through the strong chelating coordination ability of the ortho-dual dihydroxyl groups, anchor to aluminum atoms on the anolyte surface, forming a stable five-membered ring chelate, effectively passivating interfacial active sites. The borate ester groups utilize the Lewis acid center of boron atoms to help reduce the free water activity of the system, while their large steric hindrance creates a shielding effect on adjacent ester bonds, synergistically enhancing the polyester backbone's resistance to thermal degradation and hydrolysis.
[0032] Meanwhile, the aluminum-phosphate complex solvent formed by the coordination reaction of aluminum alkoxide and alkyl phosphate in polyol medium not only has a high boiling point and excellent thermochemical inertness, but its Al-OP coordination structure can also tend to accumulate at the defects of anodic oxide film under the induction of electric field. It can form an inorganic nano-protective layer containing AlPO4 through in-situ hydrolysis and condensation. This layer, together with the organic polyester network, repairs the microcracks of the oxide film and resists the chemical corrosion of high temperature acidic media. In the additive system, the hydrogen-removing and water-repellent dual-effect agent composed of PEG grafted with 1,4-dihydroxyanthraquinone-2-carboxylic acid captures active hydrogen atoms during cathodic polarization through the electrochemically reversible redox properties of the anthraquinone group, which helps to compete for hydrogen evolution pathways from a reaction kinetics perspective. At the same time, the flexible long chain of PEG forms a hydrogen bond network with water molecules in the system through ether oxygen atoms, which improves the wettability of the electrode interface and slows down the diffusion and penetration of water molecules to the anodic oxide film interface. The ortho-hydroxyl groups in the 1,4-dihydroxyanthraquinone structure weaken the hydration attack of water molecules on the oxide film through hydrogen bonding, synergistic effect with the catechol-boron ester skeleton and AlPO4 shielding layer. Attached Figure Description
[0033] Figure 1 This is a physical image of a long-life, high-voltage aluminum electrolytic electrolyte composition according to Example 3. Detailed Implementation
[0034] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the embodiments of this application. Obviously, the embodiments described below are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0035] The terminology used in this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application.
[0036] The singular forms “for,” “or,” “a,” “any,” and “the” used in this application are intended to include the plural forms unless the context clearly indicates otherwise.
[0037] Furthermore, the terms "first" and "second" appearing in this application are for descriptive purposes only and should not be construed as indicating or implying relative importance.
[0038] The present application will be further described below with reference to the accompanying drawings, specific embodiments and comparative examples, and the specific implementation of the present application will be described in further detail.
[0039] Example 1
[0040] This embodiment provides a method for preparing a long-life, high-voltage aluminum electrolysis electrolyte composition, comprising the following steps:
[0041] S1. Adipic acid, 1,3-propanediol, and trimethylolpropane in a mass ratio of 100:55:3 are mixed to obtain a mixture. 0.1% (by mass) of p-toluenesulfonic acid is added to the mixture, and the mixture is subjected to esterification and polycondensation at 160°C for 8 hours under nitrogen protection to obtain a low-branched polyester intermediate. 8% (by mass) of 3,4-dihydroxybenzoic acid and 0.5% (by mass) of p-toluenesulfonic acid are added to the low-branched polyester intermediate, and the mixture is subjected to grafting reaction at 120°C under nitrogen protection, dehydration under reduced pressure of -0.06 MPa, and for 5 hours. 4% (by mass) of boric acid is added to the low-branched polyester intermediate, and the mixture is subjected to esterification at 80°C for 4 hours. Low-boiling substances are removed under reduced pressure at -0.08 MPa and 120°C for 1 hour to obtain a catechol-boron ester hybrid low-branched polyester.
[0042] S2. Ethylene glycol and aluminum isopropoxide were mixed and dissolved at 50°C for 1.5 h, and monobutyl phosphate was added dropwise at a rate of 1 mL / min. The mixture was reacted at 50°C for 7 h under nitrogen protection. The alcohol was removed under reduced pressure at -0.06 MPa and 80°C for 1 h, and the mixture was filtered to obtain an aluminum-phosphate coordination complex solvent. The mass ratio of aluminum isopropoxide, monobutyl phosphate, and ethylene glycol was 1:1.1:1.8.
[0043] S3. 1,4-Dihydroxyanthraquinone was dispersed in a 10 wt% sodium hydroxide aqueous solution, wherein the mass ratio of 1,4-dihydroxyanthraquinone to sodium hydroxide was 1:0.8; anhydrous ethanol of equal mass to 1,4-dihydroxyanthraquinone was added, followed by 0.5% TEBA (by mass of 1,4-dihydroxyanthraquinone). Chloroform was added dropwise under stirring at 45°C and 300 r / min, wherein the mass ratio of chloroform to 1,4-dihydroxyanthraquinone was 1:1. The two-phase reaction was carried out under reflux and condensation at 60°C for 7 h. After the reaction was completed, the mixture was cooled, the pH was adjusted to 2, a solid precipitated, separated, washed, and purified to obtain 1,4-dihydroxyanthraquinone-2-formaldehyde; the 1,4-dihydroxyanthraquinone-2-formaldehyde was dispersed in a mixed medium of acetic acid and water, wherein the mass ratio of 1,4-dihydroxyanthraquinone-2-formaldehyde to the mixed medium was 1:15, and the volume ratio of acetic acid to water was 1:1. Glacial acetic acid was used to adjust the mixture... At pH 3, 25% (by weight) of 2-methyl-2-butene (based on the mass of the 1,4-dihydroxyanthraquinone) was added, along with a 10 wt% sodium chlorite aqueous solution, wherein the amount of sodium chlorite added was 45% (by weight of the 1,4-dihydroxyanthraquinone-2-carboxaldehyde). The mixture was stirred and oxidized at 10°C for 6 hours, maintaining the pH at 3.0 throughout the process. After the reaction was complete, the mixture was cooled, and the precipitated solid was filtered, washed with water, and dried to obtain 1,4-dihydroxyanthraquinone. -2-Carboxylic acid; Under nitrogen protection, 1,4-dihydroxyanthraquinone-2-carboxylic acid, PEG-400 and p-toluenesulfonic acid were mixed, wherein the mass ratio of 1,4-dihydroxyanthraquinone-2-carboxylic acid and PEG-400 was 1:2, and the amount of p-toluenesulfonic acid added was 0.5% of the mass of 1,4-dihydroxyanthraquinone-2-carboxylic acid. The mixture was dehydrated under reduced pressure of -0.06 MPa and esterified at 130 °C for 6 h to obtain a hydrogen-removing and waterproofing dual-effect agent;
[0044] S4. The catechin-boron ester hybrid low-branched polyester, aluminum-phosphate ester coordination type composite solvent, and hydrogen-removing and water-repelling dual-effect agent are added to a compounding kettle and mixed; mannitol and phosphotungstic acid are added, wherein the mass ratio of the catechin-boron ester hybrid low-branched polyester, aluminum-phosphate ester coordination type composite solvent, hydrogen-removing and water-repelling dual-effect agent, mannitol and phosphotungstic acid is 30:40:5:1:0.5. The mixture is stirred and mixed at 70°C for 4 hours, cooled to room temperature and filtered to obtain a long-life high-voltage aluminum electrolytic electrolyte composition.
[0045] Example 2
[0046] This embodiment provides a method for preparing a long-life, high-voltage aluminum electrolysis electrolyte composition, comprising the following steps:
[0047] S1. Adipic acid, 1,3-propanediol, and trimethylolpropane in a mass ratio of 100:60:5 were mixed to obtain a mixture. 0.3% (by mass) of p-toluenesulfonic acid was added to the mixture, and the mixture was subjected to esterification and polycondensation at 175°C for 6 hours under nitrogen protection to obtain a low-branched polyester intermediate. 13% (by mass) of 3,4-dihydroxybenzoic acid and 0.7% (by mass) of p-toluenesulfonic acid were added to the low-branched polyester intermediate, and the mixture was subjected to grafting reaction at 130°C under nitrogen protection, dehydration under reduced pressure of -0.085 MPa, and for 4 hours. 7% (by mass) of boric acid was added to the low-branched polyester intermediate, and the mixture was subjected to esterification at 87°C for 3 hours. Low-boiling substances were removed under reduced pressure at -0.09 MPa and 130°C for 0.8 hours to obtain a catechol-boronic acid ester hybrid low-branched polyester.
[0048] S2. Diethylene glycol and aluminum sec-butoxide were mixed and dissolved at 65°C for 1 h, and dibutyl phosphate was added dropwise at a rate of 1.5 mL / min. The mixture was reacted at 65°C for 6 h under nitrogen protection. The alcohol was removed under reduced pressure at -0.07 MPa and 90°C for 0.7 h, and the mixture was filtered to obtain an aluminum-phosphate coordination complex solvent. The mass ratio of aluminum sec-butoxide, dibutyl phosphate, and diethylene glycol was 1:1.4:2.4.
[0049] S3. 1,4-Dihydroxyanthraquinone was dispersed in a 20 wt% sodium hydroxide aqueous solution, wherein the mass ratio of 1,4-dihydroxyanthraquinone to sodium hydroxide was 1:1.1; anhydrous ethanol (twice the mass of 1,4-dihydroxyanthraquinone) and TBAB (1.2% by mass of 1,4-dihydroxyanthraquinone) were added, and chloroform was added dropwise under stirring at 50°C and 400 r / min, wherein the mass ratio of chloroform to 1,4-dihydroxyanthraquinone was 1:1.4. The two-phase reaction was carried out under reflux and condensation at 65°C for 5 h; after the reaction was completed, the mixture was cooled, the pH was adjusted to 3, a solid precipitated, separated, washed, and purified to obtain 1,4-dihydroxyanthraquinone-2-formaldehyde; the 1,4-dihydroxyanthraquinone-2-formaldehyde was dispersed in a mixed medium of acetic acid and water, wherein the mass ratio of 1,4-dihydroxyanthraquinone-2-formaldehyde to the mixed medium was 1:30, and the volume ratio of acetic acid to water was 1:2, using ice... The pH was adjusted to 4 with acetic acid, and 40% (by weight) of 2-methyl-2-butene (based on the mass of the 1,4-dihydroxyanthraquinone) was added. A 15 wt% sodium chlorite aqueous solution was also added, with the amount of sodium chlorite in the aqueous solution being 65% of the mass of 1,4-dihydroxyanthraquinone-2-carboxaldehyde. The mixture was stirred and oxidized at 20°C for 4 hours, maintaining the pH at 4.5 throughout the process. After the reaction was complete, the mixture was cooled, and the precipitated solid was filtered, washed with water, and dried to obtain 1,4-dihydroxyanthraquinone-2-carboxaldehyde. Anthraquinone-2-carboxylic acid; under nitrogen protection, 1,4-dihydroxyanthraquinone-2-carboxylic acid, PEG-400 and p-toluenesulfonic acid were mixed, wherein the mass ratio of 1,4-dihydroxyanthraquinone-2-carboxylic acid and PEG-400 was 1:3, and the amount of p-toluenesulfonic acid added was 2% of the mass of 1,4-dihydroxyanthraquinone-2-carboxylic acid. The mixture was dehydrated under reduced pressure of -0.07 MPa and esterified at 140 °C for 4 h to obtain a hydrogen-removing and water-repellent dual-effect agent;
[0050] S4. The catechol-boron ester hybrid low-branched polyester, aluminum-phosphate ester coordination type composite solvent, and hydrogen-removing and water-repelling dual-effect agent are added to a compounding kettle and mixed; sorbitol and phosphomolybdic acid are added, wherein the mass ratio of the catechol-boron ester hybrid low-branched polyester, aluminum-phosphate ester coordination type composite solvent, hydrogen-removing and water-repelling dual-effect agent, sorbitol and phosphomolybdic acid is 40:50:10:3:1.5. The mixture is stirred and mixed at 80°C for 3 hours, cooled to room temperature and filtered to obtain a long-life high-voltage aluminum electrolytic electrolyte composition.
[0051] Example 3
[0052] A method for preparing a long-life, high-voltage aluminum electrolysis electrolyte composition includes the following steps:
[0053] S1. Adipic acid, 1,3-propanediol, and trimethylolpropane in a mass ratio of 100:65:8 are mixed to obtain a mixture. 0.5% (by mass) of p-toluenesulfonic acid is added to the mixture, and the mixture is subjected to esterification and polycondensation at 190°C for 4 hours under nitrogen protection to obtain a low-branched polyester intermediate. 18% (by mass) of 3,4-dihydroxybenzoic acid and 1% (by mass) of p-toluenesulfonic acid are added to the low-branched polyester intermediate, and the mixture is subjected to grafting reaction at 140°C under nitrogen protection, dehydration under reduced pressure of -0.095 MPa, and nitrogen protection for 3 hours. 10% (by mass) of boric acid is added to the low-branched polyester intermediate, and the mixture is subjected to esterification at 95°C for 2 hours. Low-boiling substances are removed under reduced pressure at -0.095 MPa and 150°C for 0.5 hours to obtain a catechol-boronic ester hybrid low-branched polyester.
[0054] S2. Wherein the aluminum alkoxide is selected from aluminum isopropoxide or aluminum sec-butoxide; the alkyl phosphate is selected from at least one of monobutyl phosphate, dibutyl phosphate, monoisooctyl phosphate, and diisooctyl phosphate; the polyol is selected from at least one of ethylene glycol, diethylene glycol, and 1,3-propanediol;
[0055] 1,3-propanediol and aluminum isopropoxide were mixed and dissolved at 80°C for 0.5 h. Monoisooctyl phosphate was added dropwise at a rate of 2 mL / min, and the reaction was carried out at 80°C for 4 h under nitrogen protection. The alcohol was removed under reduced pressure at -0.09 MPa and 100°C for 0.5 h, and the mixture was filtered to obtain an aluminum-phosphate coordination complex solvent. The mass ratio of aluminum isopropoxide, monoisooctyl phosphate, and 1,3-propanediol was 1:1.8:3.
[0056] S3. 1,4-Dihydroxyanthraquinone was dispersed in a 30 wt% sodium hydroxide aqueous solution, wherein the mass ratio of 1,4-dihydroxyanthraquinone to sodium hydroxide was 1:1.4; anhydrous ethanol (3 times the mass of 1,4-dihydroxyanthraquinone) and TEBA (2% by mass of 1,4-dihydroxyanthraquinone) phase transfer catalyst were added; chloroform was added dropwise at 65°C and 500 r / min with stirring, wherein the mass ratio of chloroform to 1,4-dihydroxyanthraquinone was 1:1.8; the two-phase reaction was carried out at 70°C under reflux and condensation for 4 h; after the reaction was completed, the mixture was cooled, the pH was adjusted to 4, a solid precipitated, separated, washed, and purified to obtain 1,4-dihydroxyanthraquinone-2-formaldehyde; the 1,4-dihydroxyanthraquinone-2-formaldehyde was dispersed in a mixed medium of acetic acid and water, wherein the mass ratio of 1,4-dihydroxyanthraquinone-2-formaldehyde to the mixed medium was 1:40, and the volume ratio of acetic acid to water was 1:4; ice was used for the reaction. Acetic acid was used to adjust the pH to 5.5. Then, 60% (by weight) of 2-methyl-2-butene (based on the mass of the 1,4-dihydroxyanthraquinone) was added, along with a 20 wt% sodium chlorite aqueous solution, wherein the amount of sodium chlorite added was 85% of the mass of 1,4-dihydroxyanthraquinone-2-carboxaldehyde. The mixture was stirred and oxidized at 30°C for 3 hours, maintaining the pH at 5.5 throughout the process. After the reaction was complete, the mixture was cooled, and the precipitated solid was filtered, washed with water, and dried to obtain 1,4-dihydroxyanthraquinone-2-carboxaldehyde. Anthraquinone-2-carboxylic acid; under nitrogen protection, 1,4-dihydroxyanthraquinone-2-carboxylic acid, PEG-400 and p-toluenesulfonic acid were mixed, wherein the mass ratio of 1,4-dihydroxyanthraquinone-2-carboxylic acid and PEG-400 was 1:4, and the amount of p-toluenesulfonic acid added was 3% of the mass of 1,4-dihydroxyanthraquinone-2-carboxylic acid. The mixture was dehydrated under reduced pressure of -0.095 MPa and esterified at 150 °C for 3 h to obtain a hydrogen-removing and waterproofing dual-effect agent;
[0057] S4. The catechol-boron ester hybrid low-branched polyester, aluminum-phosphate ester coordination type composite solvent, and hydrogen-removing and water-repelling dual-effect agent are added to a compounding kettle and mixed; sorbitol and hypophosphite are added, wherein the mass ratio of the catechol-boron ester hybrid low-branched polyester, aluminum-phosphate ester coordination type composite solvent, hydrogen-removing and water-repelling dual-effect agent, sorbitol and hypophosphite is 50:60:15:5:3. The mixture is stirred and mixed at 90°C for 2 hours, cooled to room temperature and then filtered to obtain a long-life high-voltage aluminum electrolytic electrolyte composition.
[0058] Comparative Example 1
[0059] A method for preparing a long-life high-voltage aluminum electrolytic electrolyte composition differs from Example 3 in that after grafting 3,4-dihydroxybenzoic acid in S1, boric acid is not added for esterification reaction, i.e., the coordination crosslinking step of ortho-dihydroxyl groups of catechol with boric acid is omitted, and the low-branched polyester grafted with catechol is directly used as the polyester component. Other process parameters and operating conditions are exactly the same as in Example 3.
[0060] Comparative Example 2
[0061] A method for preparing a long-life high-voltage aluminum electrolytic electrolyte composition differs from Example 3 in that aluminum alkoxide is not added in S2, and dibutyl phosphate is directly dissolved in diethylene glycol as a single solvent component, omitting the coordination reaction step of aluminum alkoxide and alkyl phosphate. Other process parameters and operating conditions are exactly the same as in Example 3.
[0062] Comparative Example 3
[0063] A method for preparing a long-life high-voltage aluminum electrolysis electrolyte composition differs from Example 3 in that, in S3, the esterification grafting reaction of 1,4-dihydroxyanthraquinone-2-carboxylic acid and PEG-400 is not carried out. Instead, an equal mass of unmodified 1,4-dihydroxyanthraquinone-2-carboxylic acid is directly added as a hydrogen scavenger. Other process parameters and operating conditions are exactly the same as in Example 3.
[0064] Performance testing:
[0065] 1. High-temperature conductivity retention rate test: The electrolyte compositions prepared in Examples 1-3 and Comparative Examples 1-3 were injected into sealed glass electrolytic cells respectively, and the initial conductivity κ0 was measured in a constant temperature water bath at 30℃ using a conductivity meter; then the electrolyte was transferred to a polytetrafluoroethylene sealed tube and aged in a high-temperature oven at 135℃ for 1000h. After being taken out and cooled to 30℃, the conductivity κ1 was measured again, and the high-temperature conductivity retention rate η=κ1 / κ0×100% was calculated. The η values of each example and comparative example were recorded.
[0066] 2. Hydration inhibition performance test of anodic oxide film: The electrolyte compositions prepared in Examples 1-3 and Comparative Examples 1-3 were used as working electrolytes and assembled with anodized aluminum foil (formation voltage 520V) to form a simulated capacitor unit. The unit was subjected to a high-temperature load accelerated test for 1000h at 105℃ and 450V accelerating voltage. The capacitance values C0 and C1 were measured at 100Hz using an LCR digital bridge before and after the test, and the capacitance change rate ΔC=(C1-C0) / C0×100% was calculated. At the same time, the leakage current value I was read after applying the rated voltage for 2 minutes using a leakage current tester. The capacitance change rate and leakage current value of each example and comparative example were recorded.
[0067] 3. Electrolyte high-temperature pressurized gas evolution test: In an inert atmosphere glove box, 20 mL of each of the electrolyte compositions prepared in Examples 1-3 and Comparative Examples 1-3 were placed in a 50 mL stainless steel high-pressure reactor. After sealing, high-purity nitrogen was introduced into the reactor until the internal pressure was 0.2 MPa. The reactor was heated in a constant temperature oil bath at 125 °C for 24 h. After the reaction was completed, the reactor was naturally cooled to room temperature. The final pressure P1 inside the reactor was read using a precision pressure gauge. The reference pressure P0 was measured under the same conditions using an empty reactor of the same volume. The net gas evolution increment ΔP = P1 - P0 was calculated, and the ΔP values of each example and comparative example were recorded.
[0068] Table 1 Performance test data of long-life high-voltage aluminum electrolytic electrolyte compositions of Examples 1-3 and Comparative Examples 1-3
[0069]
[0070] As shown in Table 1, Examples 1 to 3 achieved improvements in high-temperature conductivity retention, resistance to hydration corrosion, and gas evolution suppression performance of the electrolyte through the molecular-level synergy of three components: catechol-boron ester hybrid low-branched polyester, aluminum-phosphate ester coordination type composite solvent, and hydrogen-removing and water-repellent dual-effect agent. Among them, Example 3 had the best matching degree of the entire set of process parameters. Except for the initial conductivity (Example 2 had the lowest at 1.62 mS / cm), all test indicators were at the best level among all groups. According to the data in Table 1, after storage at 135℃ for 1000h, Example 3 showed a conductivity retention rate η of 74.2%, a capacity change rate ΔC of only -0.7%, a leakage current of only 28μA, and a net gas evolution increment ΔP of only 0.038MPa. This indicates that the electron-deficient boron center in the catechol-boron ester hybrid network effectively captures proton impurities and free water molecules as Lewis acid sites, passivating the erosion channels of protons on the aluminum foil oxide film. At the same time, the ortho- and posterior dihydroxyl groups of catechol are anchored to aluminum ion sites on the oxide film surface through coordination bonds. Combined with the Al-P composite glassy protective layer formed in situ under the induction of an aluminum-phosphate ester coordination type composite solvent, the three synergistically achieve dynamic self-repair and interface protection of oxide film defects, fundamentally inhibiting hydration swelling and leakage current increase at high temperatures.
[0071] Compared to Example 3, Comparative Example 1 omitted the esterification reaction of boric acid after grafting with 3,4-dihydroxybenzoic acid in S1, thus skipping the coordination crosslinking step between the ortho- and ortho-dihydroxy groups of catechol and boric acid. The lack of electron-deficient centers in the borate ester enhances the ability of free water and protonated impurities to be captured by coordination, preventing the effective passivation of trace water molecules in the electrolyte and exacerbating the hydration swelling and corrosion of the anodic oxide film. Simultaneously, the absence of the steric shielding effect of the BOC covalent bond on the polyester skeleton makes the ester bonds more susceptible to thermal decomposition and hydrolysis side reactions at high temperatures, leading to an increase in the system's acid value and accelerated decline in ion conductivity. Table 1 shows that η decreased to 61.4%, ΔC expanded to -3.8%, leakage current soared to 115 μA, and ΔP reached 0.156 MPa, indicating that the borate ester crosslinking structure is the core link in constructing the interfacial water molecule capture barrier and improving the thermochemical stability of the polyester skeleton. Its absence directly leads to a comprehensive deterioration of the hydration-hydrogen evolution-thermal decomposition coupling failure.
[0072] Compared to Example 3, Comparative Example 2 did not add aluminum alkoxide in S2; instead, dibutyl phosphate was directly dissolved in diethylene glycol as a single solvent component, omitting the coordination reaction step between aluminum alkoxide and alkyl phosphate. Due to the lack of the Al-OP coordination structure, the electrolyte lost its self-repairing function of directional migration to anodic oxide film defect sites under electric field induction and the in-situ formation of an AlPO4 inorganic protective layer. Simultaneously, the uncoordinated free phosphate ester is easily hydrolyzed at high temperatures to generate small molecule phosphoric acid, which instead causes chemical corrosion to the oxide film. More importantly, the lack of the Al-OP coordination structure reduces the coordination and anchoring ability of the aluminum-phosphate coordination composite solvent for free protons and water molecules in the system. In Table 1, its η is only 55.1%, ΔC reaches -5.5%, leakage current is as high as 186μA, and ΔP is 0.142MPa. This indicates that the Al-OP coordination structure is the key component for building the dynamic self-healing ability of the oxide film and suppressing leakage current. Its absence significantly enhances the corrosion activity of the electrolyte on the aluminum substrate, and the reliability of long-term high-temperature service is seriously deteriorated.
[0073] Compared to Example 3, Comparative Example 3 did not involve the esterification grafting reaction of 1,4-dihydroxyanthraquinone-2-carboxylic acid with PEG-400 in S3. Instead, an equal mass of unmodified 1,4-dihydroxyanthraquinone-2-carboxylic acid was directly added as a hydrogen scavenger. Unmodified anthraquinone carboxylic acid lacks the covalent linkage of the flexible long chain of PEG, resulting in a significant decrease in its dispersibility in the electrolyte. The anthraquinone active centers locally aggregate due to π-π stacking, failing to achieve uniform coverage and continuous hydrogen scavenging replenishment at the cathode interface. Simultaneously, the loss of PEG segments leads to the loss of the function of the ether oxygen atoms forming a hydrogen bond network with water molecules to reduce free water activity, resulting in insufficient capture and buffering capacity for trace amounts of water in the system. In Table 1, its η is 64.7%, ΔC is -2.9%, and leakage current is 82 μA, all of which are significantly worse than those of Example 3. In particular, its ΔP is as high as 0.198 MPa, which is 4.21 times higher than 0.038 MPa in Example 3. This indicates that PEG covalent grafting is the structural basis for ensuring the long-term and efficient operation of the anthraquinone hydrogen evolution inhibition center at the electrolyte / cathode interface. Without it, the hydrogen evolution inhibition effect will decrease due to low utilization rate of active sites and uneven dispersion.
[0074] In summary, the ternary synergistic system in Examples 1 to 3 achieves synergy through three dimensions: "catechol-boronic acid ester interface anchoring and proton capture, in-situ film formation and self-repair of Al-OP coordination structure, and molecular-level dispersion and hydrogen elimination of anthraquinone-PEG covalent coupler". This synergistic effect inhibits the coupled failure chain of high-temperature thermal decomposition, hydration swelling and hydrogen evolution corrosion. The resulting long-life high-voltage aluminum electrolytic electrolyte composition can stably meet the stringent service requirements of aluminum electrolytic capacitors in high-temperature, high-voltage and long-life application scenarios.
[0075] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.
Claims
1. A long-life, high-voltage aluminum electrolytic electrolyte composition, characterized in that, Including catechol-boronic acid ester hybrid low-branched polyesters, aluminum-phosphate ester coordination type composite solvents and auxiliaries; The catechol-boronic acid ester hybrid low-branched polyester is prepared by first grafting a low-branched polyester intermediate with 3,4-dihydroxybenzoic acid esterification, and then reacting it with boric acid. The low-branched polyester intermediate is prepared by esterification polycondensation reaction of adipic acid, 1,3-propanediol and trimethylolpropane. The aluminum-phosphate coordination type composite solvent is prepared by a coordination reaction of aluminum alkoxide and alkyl phosphate in a polyol; The additives include a hydrogen-removing and waterproofing dual-effect agent, a flash voltage booster, and a high-voltage film-forming additive. The hydrogen-removing and waterproofing dual-effect agent is prepared by esterification grafting reaction of 1,4-dihydroxyanthraquinone-2-carboxylic acid and bi-hydroxyl-terminated polyethylene glycol. The 1,4-dihydroxyanthraquinone-2-carboxylic acid is prepared by formylation of 1,4-dihydroxyanthraquinone followed by oxidation with sodium chlorite.
2. The long-life high-voltage aluminum electrolytic electrolyte composition according to claim 1, characterized in that, The aluminum alkoxide is aluminum isopropoxide or aluminum sec-butoxide; the alkyl phosphate includes at least one of monobutyl phosphate, dibutyl phosphate, monoisooctyl phosphate, and diisooctyl phosphate; the polyol includes at least one of ethylene glycol, diethylene glycol, and 1,3-propanediol; the hydroxyl-terminated polyethylene glycol is PEG400; the flashover voltage booster is mannitol or sorbitol; and the high-voltage film-forming additive includes any one of phosphotungstic acid, phosphomolybdic acid, and hypophosphite.
3. A method for preparing a long-life high-voltage aluminum electrolytic electrolyte composition as described in any one of claims 1-2, characterized in that, Includes the following steps: S1. Adipic acid, 1,3-propanediol and trimethylolpropane are mixed to obtain a mixture. p-Toluenesulfonic acid is added, and an esterification polycondensation reaction is carried out under nitrogen protection to obtain a low-branched polyester intermediate. 3,4-Dihydroxybenzoic acid and p-toluenesulfonic acid are added, and a grafting reaction is carried out under nitrogen protection. Boron esterification reaction is added. Low-boiling substances are removed under reduced pressure to obtain a catechol-boron ester hybrid low-branched polyester. S2. Mix and dissolve the polyol and aluminum alkoxide, add alkyl phosphate dropwise, and react under nitrogen protection; remove alcohol under reduced pressure, filter, and obtain aluminum-phosphate coordination complex solvent; S3. 1,4-Dihydroxyanthraquinone was dispersed in an aqueous sodium hydroxide solution; anhydrous ethanol and a phase transfer catalyst were added, and chloroform was added dropwise. The two-phase reaction was carried out under reflux and condensation conditions. After the reaction was completed, the mixture was cooled, the pH was adjusted, the solid precipitated, and the solid was separated, washed, and purified to obtain 1,4-dihydroxyanthraquinone-2-carboxaldehyde. The 1,4-dihydroxyanthraquinone-2-carboxaldehyde was dispersed in a mixed medium of acetic acid and water. The pH was adjusted using glacial acetic acid, and 2-methyl-2-butene and an aqueous sodium chlorite solution were added and stirred for oxidation. After the reaction was completed, the mixture was cooled, the solid precipitated, filtered, washed with water, and dried to obtain 1,4-dihydroxyanthraquinone-2-carboxylic acid. Under nitrogen protection, 1,4-dihydroxyanthraquinone-2-carboxylic acid, PEG-400, and p-toluenesulfonic acid were mixed and grafted to obtain a hydrogen-removing and water-repellent dual-effect agent. S4. The catechin-boron ester hybrid low-branched polyester, aluminum-phosphate ester coordination type composite solvent and hydrogen-removing and waterproofing dual-effect agent are added to the compounding kettle and mixed; flash voltage booster and high voltage film-forming additive are added and stirred and mixed, cooled to room temperature and filtered to obtain a long-life high voltage aluminum electrolytic electrolyte composition.
4. The method for preparing a long-life high-voltage aluminum electrolytic electrolyte composition according to claim 3, characterized in that, In S1, the mass ratio of adipic acid, 1,3-propanediol, and trimethylolpropane is 100:(55-65):(3-8); during the esterification polycondensation reaction, the amount of p-toluenesulfonic acid added is 0.1%-0.5% of the mass of the mixture; the temperature of the esterification polycondensation reaction is 160-190°C, and the time of the esterification polycondensation reaction is 4-8 hours.
5. The method for preparing a long-life high-voltage aluminum electrolytic electrolyte composition according to claim 3, characterized in that, In S1, the amount of 3,4-dihydroxybenzoic acid added is 8% to 18% of the mass of the low-branched polyester intermediate; during the grafting reaction, the amount of p-toluenesulfonic acid added is 0.5% to 1% of the mass of the 3,4-dihydroxybenzoic acid; the process parameters of the grafting reaction are: -0.06 to -0.095 MPa vacuum dehydration, temperature 120 to 140°C, and time 3 to 5 h; the amount of boric acid added is 4% to 10% of the mass of the low-branched polyester intermediate; the temperature of the esterification reaction is 80 to 95°C, and the time of the esterification reaction is 2 to 4 h; the vacuum degree for removing low-boiling substances is -0.08 to -0.095 MPa, the temperature for removing low-boiling substances is 120 to 150°C, and the time for removing low-boiling substances is 0.5 to 1 h.
6. The method for preparing a long-life high-voltage aluminum electrolytic electrolyte composition according to claim 3, characterized in that, In S2, the dropping rate of the alkyl phosphate is 1-2 mL / min; the mixing and dissolution temperature is 50-80℃ and the mixing and dissolution time is 0.5-1.5 h; the reaction temperature is 50-80℃ and the reaction time is 4-7 h; the vacuum de-alcoholization temperature is 80-100℃ and the vacuum de-alcoholization time is 0.5-1 h; the mass ratio of the aluminum alkoxide, alkyl phosphate and polyol is 1:(1.1-1.8):(1.8-3).
7. The method for preparing a long-life high-voltage aluminum electrolytic electrolyte composition according to claim 3, characterized in that, In S3, the sodium hydroxide aqueous solution has a mass fraction of 10-30 wt%, the mass ratio of 1,4-dihydroxyanthraquinone to sodium hydroxide is 1:(0.8-1.4), and the amount of anhydrous ethanol added is 1-3 times the mass of 1,4-dihydroxyanthraquinone; the phase transfer catalyst is TEBA or TBAB, and the amount of the phase transfer catalyst added is 0.5%-2% of the mass of 1,4-dihydroxyanthraquinone; the chloroform is added dropwise at 45-65℃ and stirred at 300-500 r / min, and the mass ratio of chloroform to 1,4-dihydroxyanthraquinone is 1:(1-1.8); the temperature of the two-phase reaction is 60-70℃, the reaction time is 4-7 h, and the pH value is 2-4; the volume ratio of acetic acid to water is 1:(1-4), and the mass ratio of 1,4-dihydroxyanthraquinone-2-formaldehyde to the mixed medium is 1:(15-40).
8. The method for preparing a long-life high-voltage aluminum electrolytic electrolyte composition according to claim 3, characterized in that, In step S3, the pH value adjusted by glacial acetic acid is 3.0–5.5; the amount of 2-methyl-2-butene added is 25%–60% of the mass of 1,4-dihydroxyanthraquinone; the concentration of the sodium chlorite aqueous solution is 10–20 wt%; the amount of sodium chlorite added to the sodium chlorite aqueous solution is 45%–85% of the mass of 1,4-dihydroxyanthraquinone-2-formaldehyde; the temperature of the stirring oxidation is 10–30°C, and the stirring oxidation time is 3–6 h.
9. The method for preparing a long-life high-voltage aluminum electrolytic electrolyte composition according to claim 3, characterized in that, In S3, the mass ratio of 1,4-dihydroxyanthraquinone-2-carboxylic acid to PEG-400 is 1:(2-4), and the amount of p-toluenesulfonic acid added is 0.5% to 3% of the mass of 1,4-dihydroxyanthraquinone-2-carboxylic acid; the esterification grafting reaction is carried out under reduced pressure dehydration conditions of -0.06 to -0.095 MPa, and the temperature of the esterification grafting reaction is 130 to 150 °C, and the time is 3 to 6 h.
10. The method for preparing a long-life high-voltage aluminum electrolytic electrolyte composition according to claim 3, characterized in that, In S4, the mass ratio of the catechin-boron ester hybrid low-branched polyester, the aluminum-phosphate ester coordination type composite solvent, the hydrogen-removing and waterproofing dual-effect agent, the flash voltage booster and the high-voltage film-forming additive is (30-50):(40-60):(5-15):(1-5):(0.5-3); the stirring and mixing temperature is 70-90℃ and the time is 2-4h.